MAIN RESULTS OF FIELD STUDIES OF THE NOGAI TRADITIONAL ORNAMENT - Kuzeeva, Z Z; Murtazaev, A O; Sausev, K B (History, Archeology and Ethnography of the Caucasus, 2017)
The article presents new data on the Nogai folk ornament, obtained during expeditionary researches in the Dagestan Republic, Chechen Republic, Astrakhan Region, Karachay-Cherkess Republic, Stavropol Territory, and in Moscow and St. Petersburg in 2014 - 2016. These are materials of 83 private collections, expositions and funds of 13 central and regional museums, five archives, and four libraries. Ornamented objects of the Nogai decorative and applied art stored in museums and private collections were examined. These are mainly metal artworks of the 19th - early 20th cc., objects made of soft materials of late 19th - the 1980s, wooden objects of the first half of the 20th century. In some cemeteries of the Nogai District of the Dagestan Republic, carved stone sepulchral stelae (‘syntas’) of the19th - 20th cc. were studied. Two authors albums with traditional Nogai ornaments, unique stencils made of white paper and used as a silhouette base of patterns in felt carpets (‘kiyiz’) and for decoration of clothes, head-dresses, tobacco pouches, shoes, pillows, and blankets were revealed during the field studies and recorded. During the research, all the revealed objects of the Nogai decorative and applied art with traditional ornament were photographed, their detailed inventory and large-scale sketches were made. The stencil patterns and drawings from the albums were copied. As a result of the researches in 2014 - 2016, a database of the Nogai folk ornament has been replenished with 942 objects and 1102 kinds of stencils and drawings.
Keywords: Nogais; ornament; field studies; museum and archival materials